MATERNAL AND FETAL OUTCOMES IN EMERGENCY VERSUS ELECTIVE TWO OR MORE PREVIOUS CAESAREAN DELIVERIES - Rasheed, Faris A; Najim, Thikra; AL-Raheem, Yousif A (AL-Kindy College Medical Journal, 2010)
Background: Women with previous two ormore caesarean deliveries are usuallymanaged by elective cesarean section to avoidthe possible risks of labor. Objective: To compare the relative risks ofmaternal and fetal outcomes in emergencyversus elective previous two or morecaesarean deliveriesDesign: Randomized prospective clinicalstudySetting: Al-Elweya Maternity TeachingHospital, from 1st of March to 31st ofSeptember 2008.Methods: The study groups, those who hadprevious two or more caesarean deliveries,were included from the hospital admissions.The 1st group (102 women) presented in laborand was managed by caesarean delivery assoon as it was possible. The second group (78women) was admitted for elective cesareandelivery.The main maternal outcomes were intraoperative complications, includinghysterectomy, scar dehiscence, bladderinjuries, uterine and internal iliac arteriesligation, and blood transfusion. Postoperativematernal outcomes were severe morbidityincluding bleeding, fever, urinary tractinfection, blood transfusion, the need toIntensive Care Unit admission andreadmission. The fetal outcomes measureswere Apgar score at one and five minutes,respiratory distress syndrome (RDS),admission to the neonatal intensive care unitand fetal loss up to hospital discharge.Results: Both groups were comparable indemographic, social and past obstetric historycharacteristics. Intra operative complicationsshowed significant difference in boweladhesions (RR 0.35, 95% CI 0.14- 0.88), andblood transfusion (RR 0.51, 95% CI 0.28-0.94). There was statistical significantdifference in the mobilization time 7.2 hoursand 9.3 hours in emergency and electivegroups respectively (p= 0.0009), also infeeding time, it was shorter after emergencycaesarean section (P=0.0224), and in thehospital stay 24.6 and 32.6 hours respectively(p=0.0001). There was no statistical differencein post operative complications. Fetaloutcomes showed no statistical significantdifference in fetal loss, respiratory distress andreadmission.Conclusion: Women with previous two ormore caesarean deliveries can wait untilstarting labor for doing cesarean deliverywithout increasing risks to the mother andfetus.